Mechanical circulatory support with Impella in percutaneous coronary intervention: current status - Baskaran Chandrasekar (American Heart Journal Plus, 2021)
In patients with, or at risk of, hemodynamic instability during percutaneous coronary intervention, maintaining perfusion of vital organs is crucial. The intra-aortic balloon pump and Impella are the two most commonly used percutaneous mechanical circulatory support devices. Intra-aortic balloon pump has been in widespread use for over three decades. Mechanical circulatory support with Impella is being used increasingly often in patients with acute myocardial infarction complicated by cardiogenic shock, and in those undergoing high-risk percutaneous coronary intervention. Besides improving cardiac output and coronary perfusion, Impella has potential myocardial protective effects. Three key measures that determine the clinical utility of a device are clinical outcome, device-related complications, and cost impact. In this review, the current data on use of Impella in patients with acute myocardial infarction complicated by cardiogenic shock, in left ventricular unloading in acute myocardial infarction, and in those undergoing high-risk percutaneous coronary intervention is analyzed.